Bad but Stable: What Keeps the Russian Regions Afloat?. Issue 4 (3rd July 2016) - Zubarevich, Natalia
Abstract : Russia's fiscal system was destabilized in 2015 because of the fall in national oil revenues. The budget crisis resulted in a sustained fall in personal income, which in turn led to a fall in consumption. This in turn resulted in a decline in trade and investment. These trends were present in the majority of Russia's regions. Russia's industrial slump, on the other hand, was relatively small and did not last long, in large part due to continued investment and growth in the defense industry. The sustained industrial production, combined with the buffer of a substantial pool of foreign migrant labor, allowed for stable employment figures. Overall, the Russian economy was better able to adapt to the deterioration in conditions than most expected.